Possible Neuropathology of Sleep Disturbance Linking to Alzheimer’s Disease: Astrocytic and Microglial Roles - Xiao, Shu-Yun; Liu, Yi-Jie; Lu, Wang; Sha, Zhong-Wei; Xu, Che; Yu, Zhi-Hua; Lee, Shin-Da (Frontiers in Cellular Neuroscience, 2022)
Sleep disturbances not only deteriorate alzheimer’s disease (AD) progress by affecting cognitive states but also accelerate the neuropathological changes of AD. Astrocytes and microglia are the principal players in the regulation of both sleep and AD. We proposed that possible astrocyte-mediated and microglia-mediated neuropathologic changes of sleep disturbances linked to AD, such as astrocytic adenosinergic A1, A2, and A3 regulation; astrocytic dopamine and serotonin; astrocyte-mediated pro-inflammatory status (TNFα); sleep disturbance-attenuated microglial CX3CR1 and P2Y12; microglial Iba-1 and astrocytic glial fibrillary acidic protein (GFAP) and microglia-mediated pro-inflammatory status (IL-1b, IL-6, IL-10, and TNFα). Furthermore, astrocytic and microglial amyloid beta (Aβ) and tau in AD were reviewed such as astrocytic Aβ interaction in AD; astrocyte-mediated proinflammation in AD; astrocytic interaction with Aβ in central nervous system (CNS); astrocytic apolipoprotein E (ApoE)-induced Aβ clearance in AD as well as microglial Aβ clearance and aggregation in AD; proinflammation-induced microglial Aβ aggregation in AD; microglial-accumulated tau in AD; microglial ApoE and TREM2 in AD. We reviewed astrocytic and microglial roles in AD and sleep, such as astrocyte/microglial-mediated proinflammation in AD and sleep; astrocytic ApoE in sleep and AD; accumulated Aβ-triggered synaptic abnormalities in sleep disturbance. This review will provide a possible astrocytic and microglial mechanism of sleep disturbance linked to AD.